The Assistance (Medeplichtige) by Children Leading to the Occurrence of Criminal Acts - Prameswari, Athalie Aisyah; Harefa, Beniharmoni (Universitas Islam Sultan Agung, 2023)
This study is related to a case of assault in which the parents of the victim are prominent figures in GP Ansor. The research examines the form of complicity in the criminal act of assault committed by the underage individual, the minor AG. This research is based on the fact that legal protection relating to children in conflict with the law (ABH) has not been implemented properly. The novelty in this research is the explanation of the legal protection provided to all children who provide assistance in cases of abuse. In order to guarantee all children's rights, including children in conflict with the law, to live, grow, develop and participate optimally in accordance with human dignity, Law Number 11 of 2012 concerning the Juvenile Criminal Justice System was created. Normative juridical is used in this research through a statutory approach, using secondary data sources supported by primary and secondary legal materials. The results of the research show that according to the results of Court Decision Number 4/Pid.Sus-Anak/2023/PN.JKT.SEL which has permanent legal force, AG's child's role as a child who assists in criminal acts of abuse is appropriate, however the decision given judged by the judge to be inappropriate. Reviewing various aspects along with existing laws and regulations, it would be more appropriate to impose a second subsidiary sentence, namely Article 353 Paragraph (2) of the Criminal Code (KUHP) juncto Article 56 2nd of the Criminal Code, which reduces the sentence for AG Children, is the best choice.